The emergence of entrepreneurial ecosystems by capital, habitus, and practice: A two-phase model based on Bourdieu’s approach - Hong, Meiling; Ge, Zhenfeng; Wu, Chanti (Frontiers in Psychology, 2023)
Entrepreneurial ecosystems (EEs) are identified by intensive and coordinated entrepreneurship practices in a region. However, there is less focus on the longitudinal perspective to discover the dynamics of EE in development. This study develops a two-phase model, using Bourdieu’s approach, to show the emergence of an EE. In each phase, we identify the contents and interaction of entrepreneurship capitals, habitus, and practices. By analysing 34 interviews of technology entrepreneurs in Shenzhen, China, we find that: 1) in the heteronomous phase, pursuing economic capital and the habitus of making quick profit result in entrepreneurship practices of copycat business; 2) in the autonomous, valuing cultural capital and the habitus of making altruism result in entrepreneurship practices of innovation activity. This study offers practical implications for practitioners. First, public sectors invest in industries with high technology affordance that can create entrepreneurship opportunities. Second, social events transform entrepreneurship practices from distributed individual level to coordinated social construction.